THERMAL MODEL FOR ELECTROMAGNETIC LAUNCHERS - Zhao, H.; Souza, J. A.; Ordonez, J. C. (Revista de Engenharia Térmica, 2008)
This paper presents a 3D model for the determination of the temperature field in an electromagnetic launcher. The large amounts of energy that are dissipated into the structure of an electromagnetic launcher during short periods of time lead to a complicated thermal management situation. Effective thermal management strategies are necessary in order to maintain temperatures under acceptable limits. This paper constitutes an attempt to determine the temperature response of the launcher. A complete three-dimensional model has been developed. It combines rigid body movement, electromagnetic effects and heat diffusion together. The launcher consists of two parallel rectangular rails and an armature moving between them. Preliminary results show the current distribution on the rail cross-section, the localized resistive heating, and the rail transient temperature response. The simulation results are compared to prior work presented for a 2D geometry by Powell and Zielinski (2008).